2019
DOI: 10.1016/j.resuscitation.2019.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalography-based power spectra allow coma outcome prediction within 24 h of cardiac arrest

Abstract: Background: Outcome prediction in comatose patients following cardiac arrest remains challenging. Here, we assess the predictive performance of electroencephalography-based power spectra within 24 h from coma onset. Methods: We acquired electroencephalography (EEG) from comatose patients (n = 138) on the first day of coma in four hospital sites in Switzerland. Outcome was categorised as favourable or unfavourable based on the best state within three months. Data were split in training and test sets. We evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 20 publications
2
20
1
Order By: Relevance
“…Alpha (8)(9)(10)(11)(12) Hz) is linked to normal, tonic firing mode of the thalamus, which represents normal integrity of the corticothalamic circuit. Our results are consistent with the reports of previous EEG spectral analysisbased studies on CA survivors, which revealed that the patients who showed the presence of alpha and theta frequency bands while undergoing continuous EEG monitoring after CA had favourable outcome as opposed to the patients with a lower frequency band [26,27]. In line with these studies,…”
Section: Discussionsupporting
confidence: 93%
“…Alpha (8)(9)(10)(11)(12) Hz) is linked to normal, tonic firing mode of the thalamus, which represents normal integrity of the corticothalamic circuit. Our results are consistent with the reports of previous EEG spectral analysisbased studies on CA survivors, which revealed that the patients who showed the presence of alpha and theta frequency bands while undergoing continuous EEG monitoring after CA had favourable outcome as opposed to the patients with a lower frequency band [26,27]. In line with these studies,…”
Section: Discussionsupporting
confidence: 93%
“…Alpha oscillations are the salient features during resting or wakefulness, and the change of alpha frequency is related to aging, cognitive function, sensorimotor processing, sleep, and neurodegenerative disease including Alzheimer's disease [38][39][40] . A recent study with OHCA patients reported that the unfavorable outcome group showed lower power spectra in around 10Hz alpha frequency compared with the favorable outcome group 41 . Furthermore, another study found that the prominent alpha peaks were presented in patients with minimally conscious states and in none of the comatose patients 42 .…”
Section: Discussionmentioning
confidence: 93%
“…Alpha oscillations are the salient features during resting or wakefulness, and the change of alpha frequency is related to aging, cognitive function, sensorimotor processing, sleep, and neurodegenerative disease including Alzheimer’s disease 38 40 . A recent study with OHCA patients reported that the unfavorable outcome group showed lower power spectra in around 10 Hz alpha frequency compared with the favorable outcome group 41 . Furthermore, another study found that the prominent alpha peaks were presented in patients with minimally conscious states and in none of the comatose patients 42 .…”
Section: Discussionmentioning
confidence: 93%